On the Mars field: Antonii Radyvylovskyi’s wartime sermons and genre tradition of battle exhortation - Maksymchuk Olha (Рукописна та книжкова спадщина України, 2024)

(untitled)
The purpose of the article is to compare the thematic content of five wartime sermons by the prominent Ukrainian Baroque author Antonii Radyvylovskyi with the distinctive features of the battle exhortation, which is a common genre in the early Modern Polish literature. The study required the use of textual and comparative analysis, elements of biographical and comparative-historical methods. Scientific novelty. The study demonstrates the reading of the Ukrainian homiletic heritage of the 17th century in a cross-cultural and cross-disciplinary perspective. Conclusions. The comparative analysis displayed that the Ukrainian preacher constructs his sermons using the same rhetorical arguments as the authors of the Polish exhortations. Apparently acquainted with some literary works on war, including battle exhortations, Radyvylovskyi exploits main principles of their composing set out below. For example, in his military preaching, Radyvylovskyi extensively uses chivalric ethos with intention to represent the Ukrainian Cossack army as a knightly class, whose main aim is to serve to their lord and patria as warriors. The wartime sermons were written in the late 1670s, in the course of the confrontation between Cossacks and Moscow, on the one hand, and the Muslim empire of the Ottomans, on the other hand, so the preacher speaks about the neces sity for a Christian soldiers to defend the honor of their God and Church as well as their own. The protection of women, children, and non-military friends is obligatory for the Christian army either. Among the chivalric values needed to be defended Radyvylovskyi also mentions liberties (apparently, political and "spiritual" ones). The reward for the heroic struggles of faithful soldiers with God’s foes will be getting the everlasting glory and even the martyr’s crown in heavens. By criticizing and mocking the enemy, Radyvylovskyi demonstrates the superiority of the Christian army over the Ottoman intruders. All these and some other rhetorical commonplaces used by Antonii Radyvylovskyi make his war sermons similar to the genre of battle exhortation, although the preacher accommodates them to the Ukrainian literary process and the historical reality in the then Cossack Hetmanate.